Upaya Pemerintah Kabupaten Lamongan Dalam Melindungi Hak Cipta Batik Tradisional - Enik Isnaini (Jurnal Independent, 2013)
Batik is a traditional handicraft that contains high value of art and has been exist as the part of Indonesian (partially, Javanese) culture since long. Thus, batik, with its traditional design, including design of Lamongan traditional batik, is one of the wealth of Indonesian culture inheritance. Based on the conclusion, batik needs to be perpetuated, protected, and supported for its long goal development. As the part of the traditional culture that has been passed on since generations, patent rights of batik will be controlled by the state as it‟s been arranged in Pasal 10 ayat 2 UU No. 19 tahun 2002 about patent rights (copyrights). The emerge of falsification and imitation of traditional batik connected tightly with the economic and social condition that occurs in our society, in which after economic crisis hit our country, economic and social stability of our people slipped off unarrangedly. Patent rights protection, based on Undang Undang nomor 19 tahun 2002 about copyrights already accomodating the protection of all creations including traditional batik, yet the protection given by Undang-Undang nomor 19 tahun 2002 about copyrights aren‟t wisely, or completely, used by the apparatus.Keywords : Batik of Lamongan, Culture Inheritance, Protection of Copyrights